Nutritional management in intestinal constipation enteral nutrition therapy: a guidance guide (Research, Society and Development, 2022)
Objective: This study aimed to develop a guide of nutritional guidelines for intestinal constipation in Enteral Nutrition Therapy (ENT). Methods: Methodological development study, which describes the elaboration of an educational technology to support the therapeutic conduct. The research was carried out in three stages: The first stage consisted of a bibliographic survey in the academic databases virtual health library (VHL), Scielo and Google Scholar about the etiopathology of the syndrome; The second step was the search for enteral products, through websites, to identify dietary inputs and their composition, with indication for use in intestinal constipation, available in the national market. The third was the preparation of the nutritional management guide. Results and discussion: The guide presents: cover, back cover, presentation, summary, introduction, nutritional management and relevant information to the understanding of IC, information tables of dietary supplies available in the national market with indication for use in constipation, closing, and references. The guide included 11 formulas indicated for IC and for gastrointestinal disorders and 23 supplementary supplies, totaling 34 enteral products with claims for IC8, available on the market, and highlighting, as to fibers, pectin and guar gum, as the most predominant in enteral nutrition, and that most assist intestinal function in TNE for prolonged periods. Conclusion: The guide enables nutrition professionals to adequately manage constipation, providing relevant information about IC and suggestions for dietary inputs for use in ENT.